Prognostic significance of serum cortisol and serum albumin in patients of ischemic stroke - Fatima, Saman; Khan, Ruhi (International Journal of Advances in Medicine, 2020)
Background: Stroke is the second most common cause of mortality worldwide and a major contributor to morbidity and chronic adult disability. To study the prognostic significance of serum cortisol and serum albumin in patients of ischemic stroke was the objective. Methods: This hospital based observational cohort prospective study was undertaken in the Department of Medicine in collaboration with the Departments of Radio diagnosis and Pathology, Jawahar Lal Nehru Medical College and Hospital, AMU, Aligarh from January 2017 to November 2018. By convenience method for sampling, 102 patients who were admitted with the diagnosis of acute ischemic stroke to IPD of JNMCH, Aligarh, on clinical as well as radiological grounds were taken into study. Results: Mean cortisol was 450.84±190.35 nmol/L. The (mean±SD) of serum cortisol was 258.10±77.91 ng/ml in patients with good outcome and 585.77±113.34ng/ml in patients with poor outcome. (p<0.05, r= 0.812). Mean serum albumin was 2.83±0.76 gm/dl. The (mean±SD) of serum albumin was 3.47±0.64mg/dl in patients with good outcome and it was comparatively lower in patients with poor outcome (2.38±0.45mg/dl). (p <0.01, r=-0.659). Conclusions: Serum albumin, serum cortisol are prognostic indicators of functional outcome at 3 months in patients of ischemic stroke.